Implementing and evaluating an e-portfolio for postgraduate family medicine training in the Western Cape, South Africa - De Swardt, Magdaleen (BMC Med Educ, 2019)
BACKGROUND: In South Africa it is compulsory to submit a satisfactory portfolio of learning to gain entrance to the national exit examination of the College of Family Physicians and to qualify as a family physician. A paper-based portfolio has been implemented thus far and the need for an electronic portfolio (e-portfolio) was identified. The aim of the study was to describe and evaluate the implementation of an e-portfolio for the training of family medicine registrars in the Western Cape province of South Africa. METHODS: Mixed methods were used. A quasi-experimental study evaluated paper- and e-portfolios from the same 28 registrars in 2015 compared to 2016. Semi-structured interviews were conducted with 11 registrars or supervisors to explore their experiences of using the e-portfolio. Quantitative data was analysed in the Statistical Package for Social Sciences and qualitative data in Atlas.ti. RESULTS: Most respondents found the e-portfolio easier to use and more accessible. It made progress easier to monitor and provided sufficient evidence of learning. Feedback was made easier and more explicit. There were concerns regarding face-to-face feedback being negatively affected. It was suggested to have a feedback template to further improve feedback. Several aspects were significantly better in the e-portfolio such as feedback on the registrar’s general behaviour, alignment with learning outcomes, less feedback based on hearsay and acknowledgement of the feedback by the registrar. Although not statistically significant, there was an increase in the usage of the e-portfolio, compared to the paper portfolio. CONCLUSION: In general, the e-portfolio is an improvement on the paper-based portfolio. It is easier to access, more user-friendly and less cumbersome. It makes feedback and monitoring of progress and development of registrars easier and more visible and provides sufficient evidence of learning. Its implementation throughout South Africa is recommended. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12909-019-1692-x) contains supplementary material, which is available to authorized users.